Cross-sectional survey of resin-modified glass ionomer as dental restoration in Saudi Arabia - Mashhour Abdullah Almutairi; Amr Saad; El Homossany Mahmoud; Bassem Abuzenada (Wolters Kluwer Medknow Publications, 2022)
Introduction: Resin-modified glass ionomers (RMGI) were developed to improve the properties of glass ionomer cement. Aim: The objective is to assess the knowledge of dentists in Saudi Arabia about properties, uses, and manipulation of resin-modified glass ionomer (RMGI). Materials and Methods: An online questionnaire of 13 close-ended questions was disseminated on the internet. The survey investigated the preference for usage, cavity treatment, and both dentists' and patients' expectations. Results and Discussion: One hundred and thirty dentists have participated; and more than 99% are using RMGI occasionally with specific cases. The most common clinical use was found to be in cases of root caries and as a temporary filling material (84.6% and 61.5%, respectively). The most noticeable advantage was the fluoride release. However, the most undesirable disadvantage was the inferior esthetic compared to composite resin. It has also shown an average expectation regarding the retention, wear resistance, contouring, handling, and esthetics. Conclusion: Dentists had a good knowledge about the fluoride release ability of RMGI; however, most of the participating dentists were concerned about the esthetic and the handling of RMGI, and rarely use dentin conditioning and adhesive before RMGI placement.